2020
DOI: 10.1101/2020.09.08.20190272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional myeloid-derived suppressor cells expand in blood but not airways of COVID-19 patients and predict disease severity

Abstract: The immunopathology of COVID-19 remains enigmatic, exhibiting immunodysregulation and T cell lymphopenia. Monocytic myeloid-derived suppressor cells (M-MDSC) are T cell suppressors that expand in inflammatory conditions, but their role in acute respiratory infections remains unclear. We studied blood and airways of COVID-19 patients across disease severity at multiple timepoints. M-MDSC frequencies were elevated in blood but not in nasopharyngeal or endotracheal aspirates of COVID-19 patients compared to contr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Although M-MDSC and PMN-MDSC subsets remained unchanged in the early phase, the frequencies of PMN-MDSCs, rather than M-MDSCs, dramatically increased in the late phase of severe COVID-19 ( Fig. 1b, 1c, 2a, and 2b), reproducing ndings in recent publications [17][18][19][20][21][22] . Further extending previous ndings, we found that the increase in PMN-MDSCs was transient, and the frequencies of PMN-MDSCs returned to basal levels during the recovery phase before discharge (Fig.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Although M-MDSC and PMN-MDSC subsets remained unchanged in the early phase, the frequencies of PMN-MDSCs, rather than M-MDSCs, dramatically increased in the late phase of severe COVID-19 ( Fig. 1b, 1c, 2a, and 2b), reproducing ndings in recent publications [17][18][19][20][21][22] . Further extending previous ndings, we found that the increase in PMN-MDSCs was transient, and the frequencies of PMN-MDSCs returned to basal levels during the recovery phase before discharge (Fig.…”
Section: Resultssupporting
confidence: 87%
“…They are equipped with several immunosuppressive molecules; however, whether they are bene cial or detrimental to the clinical outcomes of cancer, obesity, and chronic infectious diseases remains unclear 8,9 . In agreement with this, several groups have recently reported the expansion of MDSC subsets in severe COVID-19 patients [16][17][18][19][20][21][22] ; however, the link between MDSC subsets and clinical outcome remains to be addressed, owing to limitations in experimental design. By separately analyzing survivors and non-survivors of severe COVID-19, we revealed the expansion of the PMN-MDSC subset as a survival-speci c event that is associated with recovery from the disease.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Although M-MDSC and PMN-MDSC subsets remained unchanged in the early phase, the frequencies of PMN-MDSCs, rather than M-MDSCs, dramatically increased in the late phase of severe COVID-19 ( Fig. 1b, 1c, 2a, and 2b), reproducing findings in recent publications [17][18][19][20][21][22] . Further extending previous findings, we found that the increase in PMN-MDSCs was transient, and the frequencies of PMN-MDSCs returned to basal levels during the recovery phase before discharge (Fig.…”
Section: Expanded Pmn-mdsc Subset In Survivors Of Severe Covid-19supporting
confidence: 88%